Wideband signal DOA estimation method based on keystone transform. Issue 21 (25th September 2019) - Wang, Ning; Zhou, Ming; Zhong, Bing; Li, Siming; Chen, Yawei
Abstract : Here, a wideband signal direction‐of‐arrival (DOA) estimation method was proposed. By applying the keystone transform, the phase difference caused by different frequency is eliminated, and then the narrowband DOA estimation method can be used directly. Compared with the traditional method, the proposed approach can achieve better estimation accuracy than incoherent subspace method and coherent subspace method at low signal‐to‐noise ratio. The theoretical derivation of the method is given. Monte–Carlo simulations are provided to demonstrate the performance of the proposed scheme.